Effect of Yogic Interventions on Perceived Stress among Guardians of Pediatric Cancer Patients in Chandigarh - kanta , Bimal; kumar , Manish; sharma , Sunil (International Research Journal of Ayurveda & Yoga, 2025)
Background: Caregivers of pediatric cancer patients often endure significant psychological stress due to prolonged caregiving demands, emotional strain, and uncertainty related to the child’s prognosis. In India, this burden is further intensified by socioeconomic and healthcare access challenges. While pharmacological treatments for stress exist, there is increasing interest in culturally grounded, holistic interventions such as Yoga for stress alleviation.